The Legal Impact of Plea Bargain in Settlement of High Profile Financial Criminal Cases in Nigeria - Paul Atagamen Aidonojie; Anne Oyenmwosa Odojor; Patience Omohoste Agbale (Faculty of Law, Sriwijaya University, Indonesia, 2021)
Plea bargain has been globally accepted as a useful criminal prosecutorial tool in accelerating the prosecution of minor criminal cases. However, it has been observed that the introduction of a plea bargain into the Nigerian criminal justice system tends to aid the ruling class in looting from the public treasury and escaping justice. Given these legal anomalies, the study used online survey questionnaires sent to four hundred and five respondents (randomly selected) residing in Nigeria in ascertaining the Nigerian citizens view on the legal effect of using a plea bargain in resolving high profile financial crime cases. Descriptive and analytical statistics were used to analyse the respondents’ responses. The study, therefore, found that though plea bargain is a useful criminal prosecutorial tool in resolving minor criminal cases, it is unsuitable in resolving high profile criminal financial cases as it tends to involve a hide and seek game which makes a mockery of the Nigeria Legal System. It is, therefore, concluded and recommended that the concept of a plea bargain in Nigeria legal system should not be used in resolving high-profile criminal financial cases, as it tends to give leverage to those looting public funds.